2022
DOI: 10.1186/s12916-022-02353-w
|View full text |Cite
|
Sign up to set email alerts
|

CoronaVac vaccine is effective in preventing symptomatic and severe COVID-19 in pregnant women in Brazil: a test-negative case-control study

Abstract: Background More doses of CoronaVac have been administered worldwide than any other COVID-19 vaccine. However, the effectiveness of COVID-19 inactivated vaccines in pregnant women is still unknown. We estimated the vaccine effectiveness (VE) of CoronaVac against symptomatic and severe COVID-19 in pregnant women in Brazil. Methods We conducted a test-negative design study in all pregnant women aged 18–49 years with COVID-19-related symptoms in Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
13
0
3
Order By: Relevance
“…In the meta-analysis fixed-effects model was used when I 2 <50%, and the random-effects model was used when the I 2 > 50% to pool the VE data with 95% confidence intervals (CIs). Among the included articles, RCT evidence from Turkey ( 16 ), Brazil ( 18 , 36 ), Indonesia ( 17 ), and the United Arab Emirates and Bahrain ( 8 ); RWE data from Chile ( 9 , 30 , 34 ), Brazil ( 19 , 24 , 27 , 35 ), Argentina ( 22 ), Thailand ( 21 ), Serbia ( 23 ), United Arab Emirates ( 25 , 31 ), Iran ( 26 ), China ( 20 , 28 , 29 ), Colombia ( 33 ), Hungary, and Turkey ( 32 ) were included. As the heterogeneity among RCT and RWE was huge, and I 2 was consistently higher than 90%, this study was not able to pool efficacy and effectiveness data together; therefore, we have done subgroup analysis for RCT and RWE studies of adult, and for the elderly and children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meta-analysis fixed-effects model was used when I 2 <50%, and the random-effects model was used when the I 2 > 50% to pool the VE data with 95% confidence intervals (CIs). Among the included articles, RCT evidence from Turkey ( 16 ), Brazil ( 18 , 36 ), Indonesia ( 17 ), and the United Arab Emirates and Bahrain ( 8 ); RWE data from Chile ( 9 , 30 , 34 ), Brazil ( 19 , 24 , 27 , 35 ), Argentina ( 22 ), Thailand ( 21 ), Serbia ( 23 ), United Arab Emirates ( 25 , 31 ), Iran ( 26 ), China ( 20 , 28 , 29 ), Colombia ( 33 ), Hungary, and Turkey ( 32 ) were included. As the heterogeneity among RCT and RWE was huge, and I 2 was consistently higher than 90%, this study was not able to pool efficacy and effectiveness data together; therefore, we have done subgroup analysis for RCT and RWE studies of adult, and for the elderly and children.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 54 studies under full-text review, 34 studies were excluded (Figure 2). Ultimately, with four records identified through other sources included, the metaanalysis comprised 24 eligible studies finally, including four phase 3 studies (8, 16-18) and 20 real-world studies (9,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (including 2 RWE shared by company). The studies mentioned virus strains were as follows: four of Alpha (22,23,31,32), one of Beta (31), three of Gamma (19,22,27), five of Delta (20,21,25,28,29), one of Omicron (30), while the others did not mention the virus type.…”
Section: Meta Analysis Of Vaccine Effectivenessmentioning
confidence: 99%
“…In the global clinical trial of ChAdOx1 nCoV‐19, the pregnancy outcome analysis of 50 women who were pregnant after vaccination showed no effect on fertility rates and pregnancy outcomes by vaccination before pregnancy 21 . The investigation of CoronaVac in pregnant women showed that two doses were 41% effective against symptomatic COVID‐19 and 85% effective against severe COVID‐19 22 . Based on the clinical safety data of pregnant women vaccination, public health institutions globally have recommended COVID‐19 vaccination for pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of COVID-19, a fourth dose of vaccine has been offered in Israel to its population above 60 years and health care workers [ 270 ], though there are reports that the fourth dose of mRNA vaccine does not offer any additional protection against new variants such as Omicron [ 271 ]. Ultimately, boosters are helpful from the perspective of the general population, but adverse immune mediated side effects should be weighed properly before widely introducing the booster doses [ 251 ]. This is particularly true in the case of immunocompromised individuals, among whom an investigation has demonstrated lower effectiveness of mRNA vaccination, in comparison to immunocompetent individuals [ 272 ].…”
Section: Immunomodulatory Approaches For Combating Covid-19 and Evdmentioning
confidence: 99%